Use of Reflectance Confocal Microscopy for Hidrocystomas: An Emerging, Cost-Effective, and Powerful Tool - Amanda Walker; Vikram Nath Sahni; Dev Ram Sahni; Julia Curtis (Case Reports in Dermatological Medicine)
Reflectance confocal microscopy (RCM) is an emerging and noninvasive imaging tool in dermatological practice. Benefits of this modality include differentiation between benign and malignant skin lesions, prevention of unnecessary biopsies, and cost effectiveness. However, RCM findings for benign lesions are rarely reported in the literature. We describe a case of reflectance confocal microscopy findings of a hidrocystoma and review potential applications of this imaging technique in everyday clinical practice.